The Imprint of Extreme Climate Events in Century-Long Time Series of Wood Anatomical Traits in High-Elevation Conifers - Carrer, Marco; Brunetti, Michele; Castagneri, Daniele (Frontiers in Plant Science, 2016)
Extreme climate events are of key importance for forest ecosystems. However, both the inherent infrequency, stochasticity and multiplicity of extreme climate events, and the array of biological responses, challenges investigations. To cope with the long life cycle of trees and the paucity of the extreme events themselves, our inferences should be based on long-term observations. In this context, tree rings and the related xylem anatomical traits represent promising sources of information, due to the wide time perspective and quality of the information they can provide. Here we test, on two high-elevation conifers (Larix decidua and Picea abies sampled at 2100 m a.s.l. in the Eastern Alps), the associations among temperature extremes during the growing season and xylem anatomical traits, specifically the number of cells per ring (CN), cell wall thickness (CWT) and cell diameter (CD). To better track the effect of extreme events over the growing season, tree rings were partitioned in 10 sectors. Climate variability has been reconstructed, for 1800-2011 at monthly resolution and for 1926-2011 at daily resolution, by exploiting the excellent availability of very long and high quality instrumental records available for the surrounding area, and taking into account the relationship between meteorological variables and site topographical settings. Summer temperature influenced anatomical traits of both species, and tree-ring anatomical profiles resulted as being associated to temperature extremes. Most of the extreme values in anatomical traits occurred with warm (positive extremes) or cold (negative) conditions. However, 0% - 34% of occurrences did not match a temperature extreme event. Specifically, CWT and CN extremes were more clearly associated to climate than CD, which presented a bias to track cold extremes. Dendroanatomical analysis, coupled to high-quality daily-resolved climate records, seems a promising approach to study the effects of extreme events on trees, but further investigations are needed to improve our comprehension of the critical role of such elusive events in forest ecosystems.